Métodos alternativos e menos invasivos para o biomonitoramento ambiental: revisão sistemática e adaptação de glicosímetros portáteis para estudos com anfíbios - Valala, Mariana Tábata Oschvat (Universidade Federal de São Carlos, 2023)
Amphibians are a group of vertebrates that have had a great decline in recent years due to the great anthropic interference in the environment, causing loss of habitat, inclusion of invasive species and the manifestation of diseases. These factors contributed to the extension of species and the decrease of different individuals. With these problems in mind, there is an increasing concern to conduct minimally invasive research, preserving the integrity and well-being of the specimens as much as possible, and providing quality research with satisfactory results. Therefore, for this master's thesis, a systematic review was carried out plus a scientometric analysis of scientific articles on alternative less invasive methods (which totaled 61 articles). In addition, an analysis was made of how portable glucometers can be adapted to studies with amphibians as a less invasive method for collecting blood glucose data as a potential biomarker indicative of stress. The systemic review revealed several areas of research in which alternative and less invasive methods have been applied in studies with amphibians, including molecular analyses, morphometric measurements, molecular analyses, and marking of individuals, imaging exams, even the reuse of carcasses of animals that were run over on roads to obtain biological certification. Despite the application of these methods, there is an urgent need for incentives for scientists to expand the adaptation of these methodologies in their studies, especially in the areas of environmental monitoring and ecotoxicology, in which the use of animal models is frequent. In the second chapter of the dissertation, the comparison between the blood glucose values between males and females of R.ictérica showed that there was no significant difference between the sexes for the values obtained through the portable glucometer (F = 1.15; p = 0.63 ), followed by the biochemical analytical method (F = 1.047; p = 0.66), indicating homogeneous glycemic values. When grouping the data of each as independent, the mean blood glucose values were similar (F = 1.050; p = 0.4819), which did not occur when dependent, showing difference in incidence (p < 0.0001; r = 0.979). Thus, it was shown that the glucometer is efficient, but tends to overestimate the glycemic levels.
Alternative and less invasive methods for environmental biomonitoring: systematic review and adaptation of portable glucosimeters for studies with amphibians
Keywords: Anuros; Extinção; Biomarcadores Alternativos; Métodos Não - Destrutivos; Revisão Sistemática; Anuran; Extinction; Alternative Biomarkers; Non - Destructive Methods; Systematic Review; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS